Family Risk Factors That Jeopardize Child Development: Scoping Review - Simões, Aida (2022)
The obligation to protect children is defined by law. However, there is fragility in identifying actual or potential situations that jeopardize their development. This review aims to identify the family risk factors that jeopardize child development. A scoping review was conducted following the Joanna Briggs Institute for Evidence-Based Practice framework and the 2020 Preferred Reporting Items for Systematic Reviews and Meta-analyses (PRISMA) statement. The research was carried out on the electronic databases PubMed, CINAHL, Nursing & Allied Health Collection: Comprehensive, MEDLINE Complete, and MedicLatina, with a time limit of 2010 to 2021. The search was restricted to documents written in Portuguese, English, and French. A total of 3998 articles were initially identified. After selecting and analysing, 28 risk factors were extracted from 29 articles. Four categories of risk factors were identified—namely, patterns of social and economic interaction, family characteristics, caregiver’s characteristics, and parenting. The results of this review allow the identification of family risk factors that jeopardize child development. This is significant for Child Protective Services workers as they carry out their risk assessments. This assessment is the first step in avoiding an accumulation of harm to at-risk children and allowing the development of interventions for minimising harm’s impact on children’s development.